2020
DOI: 10.11591/ijeecs.v18.i1.pp459-469
|View full text |Cite
|
Sign up to set email alerts
|

Radial basis function neural network for 2 satisfiability programming

Abstract: <span>Radial Basis Function Neural Network (RBFNN) is very prominent in data processing. However, improving this technique is vital for the NN training process. This paper presents an integrated 2 Satisfiability in radial basis function neural network (RBFNN-2SAT). There are two different types of training in RBFNN, namely no-training technique and half-training technique. The performance of the solutions via Genetic Algorithm (GA) training was investigated by comparing the Radial Basis Function Neural N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Step 3: Selection The chromosomes' arrangement is in a specific descending order according to the fitness function value, whereby the optimum chromosomes (i.e., of the highest value of fitness) will be kept only, whereas the remaining ones will be rejected. The selection probability, i p for each of the chromosomes, can be computed by utilizing this following equation: generated by these equations [30,12] , as well as m uniformly.…”
Section: Step 2: Computation Of Fitnessmentioning
confidence: 99%
“…Step 3: Selection The chromosomes' arrangement is in a specific descending order according to the fitness function value, whereby the optimum chromosomes (i.e., of the highest value of fitness) will be kept only, whereas the remaining ones will be rejected. The selection probability, i p for each of the chromosomes, can be computed by utilizing this following equation: generated by these equations [30,12] , as well as m uniformly.…”
Section: Step 2: Computation Of Fitnessmentioning
confidence: 99%
“…The value of H ℚ RÀkSAT signifies the value of the energy concerning the absolute final energy H min ℚ RÀkSAT obtained from random-kSAT. Hence the quality of the final neuron configuration can be properly examined based on the condition [15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] defined in equation 7jH…”
Section: Mathematical Model Of Discrete Hopfield Neural Networkmentioning
confidence: 99%
“…The study investigated the effectiveness of 2SAT logical rule in reducing the computational burden for RBFNN by obtaining the parameters in RBFNN. Successful implementation of kSAT as a logical representation in HNN has been proposed [26][27].…”
Section: Introductionsmentioning
confidence: 99%
“…The proposed methods played an important role in the emergent of several related applications such as Very Large Scale Integration (Sathasivam et al, 2020b), Bezier reconstruction (Kasihmuddin et al, 2016), logic mining (Kho et al, 2020) and many more. In another development, Alzaeemi et al (2020) proposed 2 Satisfiability logical rule in Radial Basis Function Neural Network (RBFNN) by utilizing the value of the parameters in the hidden layers. The comparative study between HNN and RBFNN has been reported in (Mansor et al 2020).…”
Section: Introductionmentioning
confidence: 99%